Pengendalian Kualitas Produk Cylinder Head Menggunakan Pendekatan QC Seven Tools dan Poka Yoke di PT Suzuki Indomobil Motor Plant Cikarang - Setyono, Fajar; Irwati, Dwi; Supriyanto, Supriyanto (DPPM UNIVERSITAS PELITA BANGSA, 2022)
PT Suzuki Indomobil Motor Plant Cikarang is a company engaged in the 4-wheeled automotive (car) sector, which carries out the assembly process from the base to becoming a car product. PT Suzuki Indomobil Motor Plant Cikarang also produces car components, one of which is a car engine component, namely Cylinder Head products. In the cylinder head component production process, there are problems with NG products sent to the next process, which is quite high, reaching 43.12% of the total NG product. From these data, further analysis was carried out, it was found that the cause was the gate cutting and baritory processes, the product inspection process was not optimal so that the NG product was sent to the next process. To deal with these problems the company uses the QC Seven Tools and poka-yoke approaches which have been carried out in the gate cutting and baritory processes by making a special jig for the Cylinder Head checking process so that the possibility of the product passing to the next process is small. The result of the improvement that has been made is the decrease in the percentage of NG products that pass to the next process to 8.33% from the previous data, which was 43.12% over a period of 4 months.